Study guides

☆☆

Q: 3x2 - 2x - 8

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x+2) - 4(x+2) = (3x-4)*(x+2)

-(3x - 4)(x - 2)

While it is possible to factor 3x2 from both of these and get 3x2(4 - 1), it's a lot easier to subtract 3x2 from 12x2 and get 9x2

It is: (-3x-4)(x+2) when factored

If you mean: x^2+2x-48 then it is (x-6)(x+8) when factored

Related questions

3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x + 2) - 4(x + 2) = (x + 2)(3x - 4).

if you rearrange it, it becomes 4y + 8 = 3x2 -2x +1 4y = 3x2 -2x -7 y= (3x2 -2x -7)/4 which is a parabola

3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x+2) - 4(x+2) = (3x-4)*(x+2)

3x2-2x-8 = (3x+4)(x-2) when factored

3x2 + 2x = 16 ∴ 3x2 + 2x - 16 = 0 ∴ 3x2 - 6x + 8x - 16 = 0 ∴ 3x(x - 2) + 8(x - 2) = 0 ∴ (3x + 8)(x - 2) = 0 ∴ x ∈ {-8/3, 2}

3x2 + 2x - 8 = 0 is a quadratic equation.

(3x+4)(x-2)

(3x + 4)(x - 2)

3x2-2x-21 = (3x+7)(x-3)

if: f(x) = x3 - 4xe-2x Then: f'(x) = 3x2 - [ 4e-2x + 2(4x / -2x) ] = 3x2 - 4e-2x + 4

-2

(3x+4)(x-2) 3x2 -6x+4x-8 3x2-2x-8

People also asked